Smart Health Safety Clothes using Motion Capture - Kyu-Ho Kim; Ki-Young Lee; Eun-Young Kang; Kyeong-Su Jang; Gyoo-Seok Choi; Jeong-Jin Kang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, the general public’s sports activities have become common and people’s scope of movement and location have become broader, so the frequency of an unexpected accident during sports and exercise activities regardless of time and place has increased accordingly. Therefore, the need of a training suit equipped with various healthcare functions was raised. There is also a growing need of smart training suit enabling the communication with various devices in accordance with the 4th Industrial Revolution era. Therefore, this study intends to design and implement a system using IoT technologies, Arduino, GPS, and motion capture technologies for a training suit that can collect and analyze various health data of the wearer and prevent the occurrence of an unexpected accident. It is expected that the wearer can check his/her own health at anytime and anywhere and reduce the risk of unexpected accidents.